2013
DOI: 10.1038/npp.2013.129
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable Effects of Kappa-Opioid Receptor Activation on Impulsive Phenotypes in Wistar Rats

Abstract: The kappa-opioid receptor (KOR) is the primary target for the endogenous opioid peptide dynorphin (DYN), and KORs reside within brain circuitry underlying the complex integration of information related to different behavioral domains such as motivation, negative affect, and decision-making. Alterations in extended amygdala DYNs and KOR function following chronic alcohol exposure have been shown to mediate escalated alcohol self-administration during acute withdrawal. In addition to excessive alcohol consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 56 publications
3
22
0
Order By: Relevance
“…2009). We have recently reported KOR activation-induce impulsive phenotypes in rats (Walker and Kissler 2013) and, well documented in both human and animal models, younger organisms engage in more impulsive and risky behaviors than their adult counterparts (Green et al . 1994;Doremus-Fitzwater et al .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…2009). We have recently reported KOR activation-induce impulsive phenotypes in rats (Walker and Kissler 2013) and, well documented in both human and animal models, younger organisms engage in more impulsive and risky behaviors than their adult counterparts (Green et al . 1994;Doremus-Fitzwater et al .…”
Section: Discussionmentioning
confidence: 96%
“…2007) and given our previous experience with the compound, nor-BNI was selected for use in the present investigations as a putative negative efficacy antagonist. We previously demonstrated a KOR specific effect of nor-BNI in the GTPγS assay (Kissler and Walker, 2015) and initiated research on KOR involvement in executive function that implicated the KOR as being an important regulator of impulse control specific to stopping an already-initiated action (Walker and Kissler, 2013). Converging lines of evidence suggested that KORs in the mPFC could be important regulators of executive function: 1) The mPFC has been implicated as a substrate for stop-signal reaction time performance (e.g., Bari et al .…”
Section: Introductionmentioning
confidence: 99%
“…75, 76 Furthermore, KOR activation was found to induce an impulsive phenotype that may contribute to the initiation of alcohol abuse and relapse in dependent individuals. 77 …”
Section: Discussionmentioning
confidence: 99%
“…mPFC KOR upregulation may contribute to deficits in PFC-dependent decision-making and cognition in alcohol and drug addiction. Furthermore, KORs increase impulsive behavior (Walker and Kissler, 2013), which is inhibited by mPFC activation. As mPFC KOR signaling is sufficient to produce aversion and necessary for KOR-mediated aversion (BalsKubik et al, 1993;Tejeda et al, 2013), it is possible that heightened PFC KOR signaling contributes to a negative affective state during abstinence.…”
Section: Discussionmentioning
confidence: 99%